DESENVOLVIMENTO E VALIDAÇÃO DE METODOLOGIA QUECHERS PARA A DETERMINAÇÃO DE TETRACICLINAS EM FRANGOS VIA HPLC UV-DAD - JOÃO VÍCTOR MORAIS GURGEL (2023)
It is evident that the development of poultry production in Brazil, particularly in the broiler sector, has made the country an important producer and exporter of chicken meat. Mainly because it is the third largest exporter of this matrix in the world. Thus, among the substances that may be present in chicken culture are antimicrobials, used both for the treatment of infectious diseases and in the form of food supplements, acting as growth promoters. In Brazil, statistics regarding the amount of antimicrobials commercialized for this purpose are few, as well as works dedicated to investigating the occurrence and environmental impact of these compounds in the environment. Thus, this work aimed to contribute to the diagnosis of contamination of environmental resources by drugs, through the optimization and validation of the QuEChERS (Quick, Easy, Cheap, Effective, Rugged, Safe) extraction method. This method represented a huge advance in relation to the preparation and extraction of the sample, allowing the analysis of a greater diversity and quantity of residues, which were analyzed by High Performance Liquid Chromatography coupled to an ultraviolet detector coupled to a diode array (DAD) for the quantification of tetracycline, oxytetracycline and chlortetracycline in chicken breast. In the optimization, a 2^7-3 fractional factorial design was applied to adjust the extraction protocol regarding the variables amount of sodium sulfate (Na2SO4), sodium chloride (NaCl), C18, PSA, Vortex time, centrifuge rotation and sampling. In the tests, matrix samples were fortified with a standard solution of tetracycline, oxytetracycline and chlortetracycline and subsequently submitted to extraction procedures. Then the method was optimized by performing another statistical study, this time using a Dohelert matrix, in order to define the best variables for extraction. Analysis of variance (ANOVA) and the lack of fit study were used to assess the significance of the data at the 95% confidence level. The performance parameters analyzed for validation were matrix effect, linearity, selectivity, precision, accuracy, limit of detection and quantification. The 2^7-3 fractional factorial design and the Dohelert matrix study provide, within the studied levels, the best option in the recovery values at a significance level of 95%, since the adjusted quadratic model uses the data satisfactorily, suggesting that the best condition for the recovery of tetracycline, oxytetracycline and chlortetracycline in chicken breast, these variables being: NaSO4= 1.00g, NaCl = 0.70g, sampling= 0.5g, vortex time: 1.0min, centrifuge rotation = 4000rpm, PSA = 100mg. The method showed adequate linearity, selectivity and accuracy, with mean recoveries of 99.1% for tetracycline, 88.7% for oxytetracycline and 84.3% for chlortetracycline. The limit of detection value obtained is 0.02mg/L for tetracycline and oxytetracycline and 0.1mg/L for chlortetracycline, in addition, the limit of quantification for the three tetracyclines was 0.1 mg/L. The validation carried out allowed us to consider that the QuEChERS method is satisfactory and presents the necessary performance characteristics, being suitable for the investigation of tetracycline residues in chicken breast.